2019
DOI: 10.21273/hortsci13732-18
|View full text |Cite
|
Sign up to set email alerts
|

Aeration Irrigation Can Improve Growth of Table Grape cv. Red Globe (Vitis vinifera L.) in Greenhouse

Abstract: Aeration through subsurface drip irrigation (SDI) can promote plant growth and increase crop yield; however, more research is focused on annual crops, and there are few studies on perennial crops. We have studied a new type of SDI (SDI with tanks) suitable for cultivation and production of perennial fruit trees and photovoltaic aeration device in greenhouse. The results showed that aeration irrigation promoted the growth of new leaves, fine roots, and new branches of grape, regulated O 2 /CO 2 content in rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In this study, in situ ventilation increased the concentration of soil O 2 and decreased that of soil CO 2 ( Figure 1 ). O 2 concentration and supply rates in the root zone plays a critical role in root respiration, root elongation, nutrient absorption and transpiration, and plant growth ( Zhao et al, 2019 ). In this process, soil bacterial and fungal communities also play vital roles in the turnover of SOC and C cycling ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, in situ ventilation increased the concentration of soil O 2 and decreased that of soil CO 2 ( Figure 1 ). O 2 concentration and supply rates in the root zone plays a critical role in root respiration, root elongation, nutrient absorption and transpiration, and plant growth ( Zhao et al, 2019 ). In this process, soil bacterial and fungal communities also play vital roles in the turnover of SOC and C cycling ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ventilation increases relative abundance of Firmicutes phyla and its Bacilli (class, family, and genus) and decreases that of Gemmatimonadetes ( Figure 4 ). It has been reported that aeration irrigation significantly increased the abundance of aerobic bacteria, such as Nitrospira and Cytophagia ( Zhao et al, 2019 ). Furthermore, the abundance of Bacillus was positively correlated with soil O 2 concentrations ( Figure 8A ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impacts of hypoxic conditions induced by mulching on soil fungal community structure have been poorly studied. Several studies have reported that aeration could significantly ameliorate the plant rhizosphere micro‐environment, raise microbial biomass, promote plant growth and yield (Li et al, 2016; Zhao et al, 2019; Zhou et al, 2020); however, such studies have mainly investigated bacterial community responses to aeration (Li et al, 2020; Zhou et al, 2020), few reports have described the link between soil O 2 content and fungal community structure to our knowledge.…”
Section: Introductionmentioning
confidence: 99%